2013
DOI: 10.2337/dc13-0307
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exogenous Glucose-Dependent Insulinotropic Polypeptide in Combination With Glucagon-Like Peptide-1 on Glycemia in the Critically Ill

Abstract: OBJECTIVEGlucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) have additive insulinotropic effects when coadministered in health. We aimed to determine whether GIP confers additional glucose lowering to that of GLP-1 in the critically ill.RESEARCH DESIGN AND METHODSTwenty mechanically ventilated critically ill patients without known diabetes were studied in a prospective, randomized, double-blind, crossover fashion on 2 consecutive days. Between T0 and T420 minutes, GLP-1 (1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
1
18
0
2
Order By: Relevance
“…Importantly, however, induction of GIP proved to be irrelevant for LPS‐dependent hyperinsulinaemia and glucose‐lowering, while this has markedly been found to be dependent on GLP‐1 . These findings are supported by recent work from Lee et al ,. showing that addition of GIP to GLP‐1 infusion does not result in additional glucose‐lowering or insulinotropic effects in critically ill patients with acute‐onset hyperglycaemia.…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, however, induction of GIP proved to be irrelevant for LPS‐dependent hyperinsulinaemia and glucose‐lowering, while this has markedly been found to be dependent on GLP‐1 . These findings are supported by recent work from Lee et al ,. showing that addition of GIP to GLP‐1 infusion does not result in additional glucose‐lowering or insulinotropic effects in critically ill patients with acute‐onset hyperglycaemia.…”
Section: Discussionsupporting
confidence: 59%
“…A proximal-distal endocrine loop that stimulates GLP-1 secretion has also been suggested. Although GIP was shown to increase GLP-1 secretion from L cells in vitro and in vivo in rodent models (Rocca and Brubaker 1999), exogenous GIP, even at high doses, does not affect plasma GLP-1 concentrations in humans (Edholm et al 2010;Lee et al 2013). In contrast, the antagonism of cholecystokinin (CCK) type 1 receptor attenuates the GLP-1 response to intraduodenal fat infusion (Beglinger et al 2010), indicating that CCK is an "upper gut signal" for the stimulation of GLP-1 secretion.…”
Section: Regulation Of Incretin Hormone Secretionmentioning
confidence: 99%
“…Blood glucose concentrations were measured and recorded immediately, by the investigators, using a blood gas analyser (ABL800 FLEX; Radiometer, Copenhagen, Denmark) [ 20 ]. The monosaccharide 3-OMG is absorbed from the small intestine via the same transporters as glucose, but is not metabolised [ 28 , 29 ], and measurement of serum 3-OMG concentrations provides an accurate measure of glucose absorption in healthy individuals and the critically ill [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our group has reported that exogenous GLP-1 retains its potent glucose-lowering effect in the critically ill patient during enteral feeding because it stimulates insulin secretion and slows gastric emptying [ 16 - 18 ]. Slower gastric emptying may be undesirable, however, particularly in relation to the potential to exacerbate gastroesophageal reflux [ 17 ] and compromise enteral feeding [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation